مدى فاعلية الإعلان الإلكتروني على زيادة نسبة المبيعات باستخدام مواقع التواصل الاجتماعي - جلبانأ. أحمد إمحمد; ناجي أ. عادل عياد ميلاد (Aljameai, 2022)
الملخص: تهدف هذه الدراسة إلى التعرف على مدى فاعلية الإعلان الالكتروني على الزبائن نحو السلع الاستهلاكية التي يتم عرضها والترويج لها على صفحات مواقع التواصل الاجتماعي. وكذلك التعرف على مدى فاعلية الإعلان الالكتروني على زيادة نسبة مبيعات أصحاب المحلات التجارية الذين يقومون بالإعلان الالكتروني على مواقع التواصل الاجتماعي. وأجريت هذه الدراسة على عينة عمديه (قصديه) متمثلة في (70) شخصاً من أصحاب المحلات التجارية الذين يقومون بإصدار إعلاناتهم الإلكترونية على مواقع التواصل الاجتماعي تحديداً بمدينة طرابلس– ليبيا. واعتمدت الدراسة على المنهج الميداني، باستخدام قائمة الاستبيان تم توزيعها على عينة الدراسة. ومن أهم النتائج التي توصلت إليها الدراسة ما يلي : قلة اهتمام بعض المعلنين بالرد على تعليقات الزبائن واستفساراتهم التي ترد في صفحات التواصل الاجتماعي. بالإضافة إلى قلة تفاعل الزبائن مع الإعلان الإلكتروني الذي يحتوي على معلومات كاملة عن السلع المعروضة بالإعلان. وبذلك توصي الدراسة أصحاب المحلات التجارية بالاهتمام الجيد بالإعلانات في صفحات التواصل الاجتماعي، والحرص على استخدام احدث وسائل وأدوات التقنية وتطبيقاتها لضمان تحقيق الهدف المطلوب من هذه الإعلانات. Abstract : This study aims to identify the effectiveness of electronic advertising on customers towards consumer goods that are displayed and promoted on the pages of social networking sites. As well as identifying the effectiveness of electronic advertising on increasing the percentage of sales of shop owners who advertise electronically on social networking sites.This study was conducted on an intentional sample of (70) shop owners who issue their electronic advertisements on social networking sites, specifically in Tripoli - Libya. The study relied on the field approach, through a list of the questionnaire.Among the most important findings of the study are the following: Lack of interest of some advertisers in responding to customers’ comments and inquiries received on social networking pages. In addition to the lack of customer interaction with the electronic advertisement that contains complete information about the goods displayed in the advertisement.Thus, the study recommends that shop owners pay good attention to advertisements on social media pages, and make sure to use and apply the latest technology and tools to ensure that the desired goal of these advertisements is achieved.